Peer Conformity and Academic Cheating: The Moderating Role of Goal Orientation and Self-Efficacy - Sahin, Arif; Sugiyo; Sunawan (Universitas Islam Indonesia, 2024)
Academic cheating is a prevalent occurrence in educational settings, having an adverse effect on both students and institutions. Therefore, this research aimed to elucidate the impact of peer conformity on academic cheating, considering the mediating factors of goal orientation and self efficacy. It focused on vocational high school students, with 477 participants selected using a purposive sampling approach. Structural Equation Modeling (SEM) was adopted for data analysis. The analysis used an established scale for academic cheating, goal orientation, and self-efficacy scales, while peer conformity scale was developed by the analysts. The results showed that there was (1) a significant correlation between peer conformity and goal orientation, (2) a positive association between peer conformity and academic cheating, (3) an influence of goal orientation on academic cheating, and (4) peer conformity indirect impact on academic cheating through mastery approach. However, no indirect effect through performance avoidance, and an indirect influence through performance approach. Further implications of the results were presented in the discussion section.